Leveraging knowledge management as the basis to achieve a sustainable competitive advantage in KwaZulu-Natal legislature - Mabaso, Thandeka Grace (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.